Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1432-2277.2009.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Obliterative bronchiolitis following lung transplantation: from old to new concepts?

Abstract: Summary Lung transplantation has come of age and is now considered a valid treatment for selected patients with end‐stage lung disease. In recent years, survival rates have much improved, although the development of chronic rejection, characterized by a progressive and irreversible decline in FEV1, which is clinically defined as bronchiolitis obliterans syndrome (BOS) remains the major obstacle to long‐term survival. Extensive research efforts with special emphasis on innate immunity have recently led to new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 63 publications
2
49
0
2
Order By: Relevance
“…Our group further refined this as only a subset of the BOS patients (NRAD) showed an increased BAL neutrophilia and IL-8, while the fBOS group showed levels comparable to stable patients (8). This study confirmed the involvement of many other proteins in BAL.…”
Section: Bile Acids In Balsupporting
confidence: 64%
See 1 more Smart Citation
“…Our group further refined this as only a subset of the BOS patients (NRAD) showed an increased BAL neutrophilia and IL-8, while the fBOS group showed levels comparable to stable patients (8). This study confirmed the involvement of many other proteins in BAL.…”
Section: Bile Acids In Balsupporting
confidence: 64%
“…Based on the response to azithromycin, our group identified the existence of at least 2 different phenotypes within BOS (8,9). The first phenotype, characterized by airway neutrophilia, FEV 1 improvement ≥10% after azithromycin treatment, an early onset and a gradual FEV 1 decline is termed Neutrophilic Reversible Allograft Dysfunction (NRAD), the other phenotype demonstrated no airway neutrophilia, no FEV 1 improvement after azithromycin thereapy, a rather late onset (after 2 years) and a rapid FEV 1 decline.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 This may be of potential clinical interest because the number of neutrophils in the airways has been associated with clinically defined BOS phenotypes following lung transplantation. 40 Increasing interest is rewarded the role of B cells in chronic GvHD. 41 Elevated blood levels of B-cell activating factor, essential for survival and differentiation of B cells, have been demonstrated in cGvHD- 42,43 and BO-patients.…”
Section: Pathogenesismentioning
confidence: 99%
“…сятся поражение дыхательных путей за счет ПДТ, ГЭР, различных инфекций, а также ишемия дыха тельных путей, вызванная механическим поврежде нием бронхиальных сосудов во время операции [14][15][16]. Эти неиммунные факторы могут вызывать по вреждение тканей и воспаление, при воздействии ко торых, в свою очередь, провоцируется и усиливается аллоиммунный ответ организма реципиента.…”
Section: клинические рекомендацииunclassified